Preparation method and application of metal atom modified folic acid derived hard carbon material

The preparation of metal atom modified hard carbon materials through hydrothermal-carbonization method solves the problem of poor rate performance of hard carbon materials in sodium ion batteries, and achieves the improvement of high specific capacity and high rate performance. At the same time, the preparation process is simplified and the reduction of Energy consumption.

CN119461332AActive Publication Date: 2025-02-18HEBEI UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411749677.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-18
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Among existing sodium ion batteries, the rate performance of hard carbon materials is poor, and the commercial preparation process requires high temperature carbonization and high energy consumption, which limits its wide application.

Method used

By using folic acid and soluble metal salts as raw materials, the hydrothermal-carbonization method is used to prepare hard carbon materials modified by metal atoms, adjust the hydrothermal reaction temperature and solvent ratio, and use the catalytic action of metal atoms to reduce the carbonization temperature and increase the hard carbon Rate performance.

Benefits of technology

The high rate performance of hard carbon materials is achieved, which is specifically manifested as reaching a specific capacity of 140 mAh g-1 at a current density of 1 A g-1, simplifying the preparation process, reducing energy consumption, and improving the stability of the material and controllability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461332A_ABST
    Figure CN119461332A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a metal atom modified folic acid derived hard carbon material. According to the method, folic acid and soluble metal salt are adopted as raw materials, and a metal atom modified hard carbon material is prepared through a hydrothermal-carbonization method; according to the method, the content of metal atoms and the microstructure of a product are controlled by regulating and controlling the temperature and the solvent ratio of the hydrothermal reaction and utilizing the chelation effect of carboxyl functional groups of folic acid and metal ions, and based on the catalytic action of the metal atoms, the carbonization temperature is reduced, the surface defects are reduced, and the interface reaction kinetics is improved, so that the rate capability of hard carbon is improved. The method disclosed by the invention has the advantages of simplicity and convenience, simple raw materials, environmental friendliness, good process repeatability, stable product quality and the like; and the rate capability of the hard carbon is shown as follows: the specific capacity of 140 mAh g <-1 > is realized under the current density of 1 A g <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and specifically to a metal single atom-modified folic acid-derived hard carbon material with high rate performance and a preparation method thereof, as well as application of the material in sodium ion batteries. Background Art

[0002] With the continuous growth of global energy demand and the urgent need for sustainable energy solutions, the research and development of new electrochemical energy storage devices has become an inevitable trend. Among them, sodium-ion batteries have become a research hotspot due to their abundant resources, low cost and environmental friendliness, but they still face challenges such as low energy density and poor rate performance. The development of advanced electrode materials is crucial to breaking through the performance bottleneck of sodium-ion batteries.

[0003] As a carbon-based negative electrode material, hard carbon has attracted much attention due to its excellent electrochemical comprehensive performance, wide raw material sources and simple preparation methods, showing high application prospects. Hard carbon has a unique microstructure, which is composed of short-range ordered carbon layers stacked in an interlaced manner, forming abundant defects and pores, as well as a large interlayer spacing, with a high capacity of 300-350mAh g -1 However, the disordered microstructure and slow interfacial reaction kinetics of hard carbon lead to its poor rate performance, and the commercial hard carbon preparation process usually includes high-temperature carbonization treatment (1400-1600℃), which consumes a lot of energy, further hindering the widespread application of hard carbon.

[0004] In the prior art, patent CN117658101A discloses a metal molybdenum-doped sodium ion battery hard carbon negative electrode material and its preparation method, wherein the hard carbon negative electrode material comprises a hard carbon matrix, a molybdenum metal source and ammonium persulfate, and the molybdenum-based doping phase is combined with the hard carbon precursor by a hydrothermal method. In the subsequent high-temperature carbonization, the molybdenum base adjusts the microstructure of the hard carbon and increases the active sites, thereby improving the reversible capacity of the hard carbon. However, the preparation method of introducing a metal doping phase into hard carbon in this technology still has limitations, for example: molybdenum-based doping requires the additional introduction of a heteroatom precursor (ammonium persulfate), and carbonization requires a higher temperature (1200~1500℃). Patent CN117446781A discloses a method for preparing a phosphorus-metal alloy co-doped hard carbon composite material, the preparation method of which is: mixing red phosphorus, a cross-linking agent and a solid phase resin by ball milling, then heating and curing at 300-500°C to obtain an intermediate, then mixing the intermediate, metal alloy powder and sodium carboxymethyl cellulose in a certain proportion and carbonizing at high temperature (1200-1500°C), thanks to the high specific capacity of the metal compound and the pore-forming effect of phosphorus, the specific capacity of the hard carbon is improved. However, the raw materials of the doped material are complex, the preparation process is cumbersome and the energy consumption is large.

[0005] Therefore, there is an urgent need to develop new preparation methods for metal atom-modified hard carbon materials that meet the characteristics of simple raw materials, high controllability and low carbonization temperature, so as to further improve the rate performance of hard carbon. Summary of the invention

[0006] The purpose of the present invention is to address the deficiencies in current technology and provide a method for preparing and applying a folic acid-derived hard carbon material modified with a metal atom. This method uses only folic acid (nitrogen-containing carbon source) and a soluble metal salt as raw materials, and prepares a metal atom-modified hard carbon material by a hydrothermal-carbonization method; that is, by regulating the temperature and solvent ratio of the hydrothermal reaction, the carboxyl functional group of folic acid is used to chelate with metal ions, the content of metal atoms and the microstructure of the product are controlled, and based on the catalytic effect of metal atoms, the carbonization temperature is lowered, surface defects are reduced, and the interfacial reaction kinetics are improved, thereby improving the rate performance of the hard carbon. The method of the present invention has the advantages of simplicity, simple raw materials, environmental friendliness, good process repeatability, stable product quality, etc. The rate performance of the hard carbon is as follows: 1 A g -1 A current density of 140 mAh g -1 Specific capacity.

[0007] The technical solution of the present invention is: A method for preparing a metal atom-modified folic acid-derived hard carbon material comprises the following steps: Step 1: Preparation of precursor solution: Adding folic acid and a water-soluble metal salt into a mixed solvent, followed by stirring and ultrasonic treatment to obtain a suspension; Wherein, in the water-soluble metal salt, the metal is iron, cobalt, nickel, copper or zinc, and the salt is nitrate or chloride; the molar ratio of folic acid powder to the water-soluble metal salt is 10:1 to 1:10, preferably, the ratio is 2:1 to 1:1; The mixed solvent is ethanol and deionized water, and the volume ratio of ethanol to water is 1-1.5:1-2. Preferably, the ratio of ethanol to water is 1:1.

[0008] Add 0.5-2.5 mmol folic acid per 60 mL of mixed solution; Step 2: Hydrothermal treatment: The suspension was transferred to a reactor, placed in a forced air drying oven, and subjected to hydrothermal treatment at 120-220°C for 1-4 hours; Step 3: Clean and dry After the hydrothermal reaction is completed, the precipitate is immersed in deionized water, placed in a centrifuge for centrifugation, and then washed; the "immersion-centrifugation-washing" cycle is repeated 2 to 4 times, and then freeze-dried overnight to obtain an intermediate; Step 4: High temperature carbonization: The intermediate obtained in step three is placed in an argon-protected quartz tube furnace and carbonized at 800-1100°C for 1-3 hours. After cooling to room temperature in the furnace, a metal atom-modified folic acid-derived hard carbon material FA-M (M represents the type of metal atom) is obtained.

[0009] In step 2, the hydrothermal temperature is preferably 120°C to 180°C In step 4, the carbonization temperature is preferably 700-1000°C.

[0010] The metal atom-modified folic acid-derived hard carbon material obtained by the method is used as an active material of a negative electrode in a sodium ion battery.

[0011] In the sodium ion battery: the positive electrode material is sodium metal, the separator is glass fiber, the electrolyte solute is 1 M sodium hexafluorophosphate (NaPF6), and the electrolyte solvent is ethylene glycol dimethyl ether (DME).

[0012] The metal single atom modified hard carbon obtained by the method can achieve higher coulombic efficiency and better rate performance when made into a sodium ion battery.

[0013] The mechanism of the present invention is: The present invention adjusts the solubility of folic acid by changing the hydrothermal temperature, and adjusts the microstructure of the hard carbon negative electrode material by metal, thereby improving the degree of graphitization of the hard carbon, increasing the conductivity, increasing the number of active sites on the surface, and improving the rate performance of the hard carbon. The specific process is: The -COOH group in the folic acid molecule is hydrolyzed in the mixed solution to produce -COO - Negatively charged, it can chelate with positively charged metal ions through electrostatic interaction, promoting the further dissolution of folic acid molecules. The dissolved folic acid molecules form precursors with specific morphology through self-assembly reactions. By changing the polarity of the solvent to control the self-assembly mode of folic acid, hard carbon with a three-dimensional porous structure can be obtained, which is beneficial to improve the infiltration of the material with the electrolyte and improve the rate performance of hard carbon. In addition, the growth of graphite micro-regions during the metal atom-catalyzed carbonization process can reduce the carbonization temperature of the material and reduce the energy consumption during the preparation process.

[0014] The present invention has the following beneficial effects: 1. The present invention proposes a method for preparing metal single atom modified hard carbon, which has the advantages of simple preparation method, simple raw materials, environmental friendliness, good process repeatability and stable product quality.

[0015] 2. By selecting folic acid containing nitrogen as the carbon source, there is no need to introduce additional heteroatom precursors, and metal atom-modified hard carbon materials are successfully obtained after hydrothermal carbonization. By changing the ratio of ethanol and water in the solvent, the self-assembly mode of folic acid is controlled to obtain hard carbon with a three-dimensional network structure, which increases the contact between the hard carbon and the electrolyte and improves the rate performance of the hard carbon.

[0016] 3. Based on the chelation between the carboxyl functional groups in folic acid and metal ions, the metal atoms are stably present in folic acid. In the subsequent carbonization process, the metal atoms catalyze the graphitization process and reduce the carbonization temperature conditions. Thanks to the electronic structure and geometric effects of the metal atoms and nitrogen coordination configuration, the conductivity of hard carbon is improved, the active sites are increased, and the rate performance of hard carbon is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a scanning electron microscope photograph of the metal atom-modified folic acid-derived hard carbon material FA-Mn prepared in Example 3; Figure 2 is the XRD image of the metal atom-modified folic acid-derived hard carbon material FA-Mn prepared in Example 3; Figure 3 is a Raman image of the metal atom-modified folic acid-derived hard carbon material FA-Mn prepared in Example 3; Figure 4 is the CV image of the metal atom-modified folic acid-derived hard carbon material FA-Mn obtained in Example 3; Figure 5 It is the rate performance image of the metal atom-modified folic acid-derived hard carbon material FA-Mn at different current densities in Example 3.

[0018] Figure 6 These are rate performance images of the folic acid-derived hard carbon material FA without metal atom modification in Comparative Example 1 at different current densities. DETAILED DESCRIPTION

[0019] The present invention is further described below by way of examples, but is not limited to the examples. The experimental methods in the examples without specifying specific conditions are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified. The raw materials required for the following examples are all commercially available.

[0020] Example 1 Step 1: Preparation of precursor solution: 1.25 mmol of folic acid and 1.25 mmol of zinc nitrate were dispersed in a 100 ml beaker, and 30 ml of ethanol and 30 ml of deionized water were added. The mixture was then stirred for 10 min and ultrasonically treated to make the suspension evenly dispersed.

[0021] Step 2: Hydrothermal treatment: The uniformly dispersed solution was transferred to a reactor, placed in a forced air drying oven, and hydrothermally carbonized at 140 °C for 3 h.

[0022] Step 3: Clean and dry After the hydrothermal reaction is completed, the precipitate is immersed in deionized water, placed in a centrifuge for centrifugation and washing. The "immersion-centrifugation-washing" cycle is repeated three times, followed by freeze drying overnight to obtain a precursor.

[0023] Step 4: High temperature carbonization: The precursor obtained in step 2 is placed in a quartz tube furnace protected by argon gas, heated to 800°C at a heating rate of 5°C / min, kept at this temperature for 2 h, and cooled to room temperature with the furnace to obtain zinc atom-modified hard carbon.

[0024] Example 2 Step 1: Preparation of precursor solution: 1.25 mmol of folic acid and 2.5 mmol of cobalt nitrate were dispersed in a 100 ml beaker, and 40 ml of ethanol and 20 ml of deionized water were added. The mixture was then stirred for 10 min and ultrasonically treated to make the suspension evenly dispersed.

[0025] Step 2: Hydrothermal treatment: The uniformly dispersed solution was transferred to a reactor, placed in a forced air drying oven, and hydrothermally carbonized at 140 °C for 3 h.

[0026] Step 3: Clean and dry After the hydrothermal reaction is completed, the precipitate is immersed in deionized water and placed in a centrifuge for centrifugal washing. The centrifugal washing is repeated three times, and then freeze-dried overnight to obtain a precursor.

[0027] Step 4: High temperature carbonization: The precursor obtained in step 2 is placed in a quartz tube furnace protected by argon gas, heated to 800°C at a heating rate of 5°C / min, and kept at this temperature for 2 h to obtain cobalt atom-modified hard carbon.

[0028] Example 3 Step 1: Preparation of precursor solution: 1.25 mmol folic acid and 1.25 mmol manganese chloride were dispersed in a 100 ml beaker, and 30 ml ethanol and 30 ml deionized water were added. The mixture was then stirred for 10 min and ultrasonically treated to make the suspension evenly dispersed.

[0029] Step 2: Hydrothermal treatment: The uniformly dispersed solution was transferred to a reactor, placed in a forced air drying oven, and hydrothermally carbonized at 140 °C for 3 h.

[0030] Step 3: Clean and dry After the hydrothermal reaction is completed, the precipitate is immersed in deionized water and placed in a centrifuge for centrifugal washing. The centrifugal washing is repeated three times, and then freeze-dried overnight to obtain a precursor.

[0031] Step 4: High temperature carbonization: The precursor obtained in step 2 is placed in a quartz tube furnace protected by argon gas, heated to 1000°C at a heating rate of 5°C / min, and kept at this temperature for 2 h to obtain manganese atom-modified hard carbon.

[0032] Figure 1 This is a scanning electron microscope image of the folic acid-derived hard carbon material FA-Mn modified with metal atoms. The material exhibits a three-dimensional network structure. Figure 2 XRD of FA-Mn, a folic acid-derived hard carbon material modified with metal atoms. The material is amorphous hard carbon. Figure 3 This is the Raman image of the folic acid-derived hard carbon material FA-Mn modified with metal atoms. The intensity ratio of the D peak to the G peak is I D / I G =0.95, with a higher degree of graphitization; Figure 4 The CV image of the folic acid-derived hard carbon material FA-Mn modified with metal atoms shows that the oxidation peak and reduction peak have similar shapes, the sodium storage reaction is reversible, and the oxidation-reduction peaks are adjacent, which indicates faster reaction kinetics. Figure 5 Rate performance images of metal atom-modified folic acid-derived hard carbon material FA-Mn at different current densities.

[0033] Example 4 Step 1: Preparation of precursor solution: 1.25 mmol folic acid and 1.25 mmol manganese nitrate were dispersed in a 100 ml beaker, and 30 ml ethanol and 30 ml deionized water were added. The mixture was then stirred for 10 min and ultrasonically treated to make the suspension evenly dispersed.

[0034] Step 2: Hydrothermal treatment: The uniformly dispersed solution was transferred to a reactor, placed in a forced air drying oven, and hydrothermally carbonized at 120 °C for 2 h.

[0035] Step 3: Clean and dry After the hydrothermal reaction is completed, the precipitate is immersed in deionized water and placed in a centrifuge for centrifugal washing. The centrifugal washing is repeated three times, and then freeze-dried overnight to obtain a precursor.

[0036] Step 4: High temperature carbonization: The precursor obtained in step 2 is placed in a quartz tube furnace protected by argon gas, heated to 1100°C at a heating rate of 5°C / min, and kept at this temperature for 2 h to obtain manganese atom-modified hard carbon.

[0037] Comparative Example 1 Step 1: Preparation of precursor solution: 1.25 mmol of folic acid was dispersed in a 100 ml beaker, and 30 ml of ethanol and 30 ml of deionized water were added, followed by stirring for 10 min and ultrasonic treatment to make the suspension evenly dispersed.

[0038] Step 2: Hydrothermal treatment: The uniformly dispersed solution was transferred to a reactor, placed in a forced air drying oven, and hydrothermally carbonized at 140 °C for 3 h.

[0039] Step 3: Clean and dry After the hydrothermal reaction is completed, the precipitate is immersed in deionized water and placed in a centrifuge for centrifugal washing. The centrifugal washing is repeated three times, and then freeze-dried overnight to obtain a precursor.

[0040] Step 4: High temperature carbonization: The precursor obtained in step 2 is placed in a quartz tube furnace protected by argon gas, heated to 1000°C at a heating rate of 5°C / min, and kept at this temperature for 2 h to obtain hard carbon.

[0041] Assemble the battery: Take 70 mg of hard carbon (the products prepared in each embodiment and comparative example), add 20 mg of super P, 10 mg of PVDF, and then add 800 ul of NMP, stir for 10 min to obtain slurry, coat it on the surface of copper foil, and dry it at 100°C for 12 h to obtain a negative electrode; The electrolyte solvent was ethylene glycol dimethyl ether, and the solute was 1 M sodium hexafluorophosphate; The positive electrode is a sodium sheet; The negative electrode, electrolyte and sodium sheet are used to assemble a button cell.

[0042] test: Rate performance test: After discharging to 0.01 V at 0.5 C, charge to 2 V at 0.5 C, and cycle for five cycles; after discharging to 0.01 V at 1 C, charge to 2 V at 1 C, and cycle for five cycles; after discharging to 0.01 V at 2 C, charge to 2 V at 2 C, and cycle for five cycles; after discharging to 0.01 V at 5 C, charge to 2 V at 5 C, and cycle for five cycles; after discharging to 0.01 V at 10 C, charge to 2 V at 10 C, and cycle for five cycles (1 C = 100 mA g -1 ). The charge specific capacity at different current densities is taken as its rate performance.

[0043] The measured results are shown in the following table (current density is 1A g -1 ):

[0044] The comparative example is a folic acid-derived hard carbon material without metal atom modification. -1 At a current density of 1.3 MW, the specific capacity is only 100 mAh g -1 Compared with the folic acid-derived hard carbon materials modified by metal atoms, their rate performance is poor. This indicates that metal atoms optimize the microstructure of hard carbon materials and improve the rate performance of hard carbon.

[0045] Figure 1 From the SEM image of the hard carbon in Example 3, it can be clearly observed that the prepared hard carbon has a three-dimensional porous network structure.

[0046] Figure 5 This is the rate performance diagram of the folic acid-derived hard carbon modified with manganese atoms prepared in Example 3. It can be seen from the figure that the hard carbon still maintains a high specific capacity at a high current density, even at 1 A g -1 At a current density of 1.34 W, the reversible capacity can still reach 140 mAh g -1 , indicating its outstanding rate performance.

[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0048] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing a metal atom-modified folic acid-derived hard carbon material, characterized in that the method comprises the following steps: Step 1: Preparation of precursor solution: Add folic acid and a water-soluble metal salt to a mixed solvent, followed by stirring and ultrasonic treatment to obtain a suspension; Wherein, in the water-soluble metal salt, the metal is iron, cobalt, nickel, copper or zinc, and the salt is nitrate or chloride; the molar ratio of folic acid to the water-soluble metal salt is 10:1 to 1:10; The mixed solvent is ethanol and deionized water, and the volume ratio of ethanol to water is 1~1.5:1~2; Add 0.5-2.5mmol folic acid to every 60mL of mixed solution; Step 2: Hydrothermal treatment: The suspension was transferred to a reactor and subjected to hydrothermal treatment at 120-220°C for 1-4 hours; Step 3: Clean and dry After the hydrothermal reaction is completed, the precipitate is immersed in deionized water, placed in a centrifuge for centrifugation, and then washed; the "immersion-centrifugation-washing" cycle is repeated 2 to 4 times, and then freeze-dried overnight to obtain an intermediate; Step 4: High temperature carbonization: The intermediate obtained in step three is placed in argon gas and carbonized at 800-1100° C. for 1-3 h. After cooling to room temperature in the furnace, a metal atom-modified folic acid-derived hard carbon material is obtained.

2. The method for preparing a metal atom-modified folic acid-derived hard carbon material according to claim 1, wherein in step 1, the molar ratio of folic acid powder to water-soluble metal salt is 2:1 to 1:1; The ratio of ethanol to water in the mixed solvent is 1:

1.

3. The method for preparing the metal atom-modified folic acid-derived hard carbon material according to claim 1, characterized in that In step 2, the hydrothermal temperature is 120°C to 180°C; in step 4, the carbonization temperature is 700°C to 1000°C.

4. Application of the metal atom-modified folic acid-derived hard carbon material obtained by the method of claim 1, characterized in that it is used as an active material for the negative electrode in a sodium ion battery.

5. The use as claimed in claim 4, characterized in that in the sodium ion battery: the positive electrode material is sodium metal, the separator is glass fiber, the electrolyte solute is 1 M sodium hexafluorophosphate (NaPF6), and the electrolyte solvent is ethylene glycol dimethyl ether (DME).

Citation Information

Patent Citations

  • Method for preparing nano-hollow spherical shell zinc oxide by hydrothermal-calcinating method

    CN102897825A

  • Hard carbon negative electrode material and preparation method and application thereof

    CN114380284A

  • Hard carbon material, preparation method thereof and application of hard carbon material in sodium-ion battery

    CN115124025A

  • Porous silicon-carbon composite negative electrode material and preparation method thereof

    CN116387487A

  • Piperazine derivative and method for producing the same

    JP2002047279A